A sustainable approach for material and metal recovery from E-waste using subcritical to supercritical methanol. (15th May 2022) - Preetam, Amrita; Mishra, Snigdha; Naik, S.N.; Pant, K.K.; Kumar, Vivek
Graphical abstract: Highlights: Depolymerization of organics of e-waste under subcritical-supercritical environment. Critical temperature and pressure of methanol is less than supercritical water. Metal recovery of precious metals and copper is greater than 90% Liquid product obtained after SCM treatment is a bromine free liquid oil. Zero percent waste discharge process. Abstract: The heterogeneous nature of e-waste, which is a rich source of metals, polymers, glass fibres and ceramics, is troublesome. Multi-step processes are employed to effectively treat e-waste with minimum environmental impact. In this research, a subcritical to supercritical methanol environment was investigated to pre-treat e-waste, recovering non-metallic fractions and eventually concentrate metals from e-waste. Experiments were conducted in the temperature range of 150 °C to 300 °C at an autogenous pressure with initial atmospheric pressure. The mechanism of depolymerization was investigated by varying reaction time from 30 min to 240 min; solid to liquid ratio of 1:10 to 1:30 g/ml in a batch reactor under N2 environment. Comparative analysis of liquid products obtained after Supercritical Methanol (SCM) treatment for both Waste Random Access Memory (WRAM) and Waste Printed Circuit Board (WPCB) was done with pyrolyzed oil/liquid product. This research briefly illustrates oil and solid product compositional changes with operating temperature, pressure, and solid/liquid ratio range. The metal concentrations of copper, nickel, silver, zinc, and gold are greater than 90% after SCM treatment. For comparison, the feed material was pyrolyzed under the same condition, the difference in oil and solid products are assessed. In the end section, the environmental and economic benefits of SCM were also discussed compared to other supercritical and conventional technologies. An efficient and greener approach of supercritical solvent is proposed via this research for e-waste recycling.